Uso de serviço odontológico na qualidade de vida relacionada à saúde bucal de crianças: um estudo de coorte - Menegazzo, Gabriele Rissotto (2018)
The attention and organization of dental services to the needs of the population helps reduce the inequities. Previous studies have demonstrated that there is an association between dental attendance and oral health-related quality of life. However, the most of these studies have a cross-sectional design, which limits cause-effect relationship. Considering that, changes in childhood reflect throughout adult life, the aim of this study was evaluate the effect of the use of routine dental care on children’s oral health-related quality of life in a south city of Brazil. This is a cohort study that has a 7-year follow-up. An epidemiological survey was performed in Santa Maria, Brazil, during the National Children’s Vaccination Day, in the years 2010. A total of 639 preschool children were examined. The second stage of this study took place in 2017, when 449 children 7-13 years-old were re-examined (cohort retention rate of 70.3%). The variables sex, maternal education, household income and household crowding were assessed in 2010 throughout a semi-structured questionnaire answered by children’s caregivers. The routine dental attendance throughout the cohort were based on two questions assessed in 2010 and in 2017. Clinical variables, like occurrence of untreated caries and maxillary overjet, were assessed in 2010 by calibrated examiners. For the assessment of the child oral health-related quality of life (COHRQoL), outcome of this study, children answered the Brazilian version of the Child Perception Questionnaire (CPQ8-10) in 2017. A multilevel Poisson regression models were used to describe the influence of the behavioral variables of use of the dental services on overall and domain specific CPQ8-10 scores. The results showed that the proportions of participants who reported worst CPQ scores were higher among those who, at some point in their life, experienced a curative dental attendance. Adjusted analysis demonstrated that the mean CPQ8-10 was two times higher for non-routine dental attendance when compared to children who were routine dental attenders (IRR: 2.05;95% CI 1.59-2.66). Analogous associations were described for the CPQ8-10 domains-specific analysis. The findings suggested that there is an impact of long-term routine attendance on COHRQoL and would warrant policy initiatives that highlight the importance of routine dental attendance.